The Analysis of On-Time Performance, Service Quality, Brand Image, and Promotion on Passenger Loyalty through Passenger Satisfaction - Yuliantini; Olfebri Olfebri; Aang Gunawan; Basri Fahriza (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The purpose of this study is to develop hypotheses related to factors that influence passenger loyalty, especially in the aviation sector. The approach used in this literature review is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach were obtained from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage Q2-Q4, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. The results of this literature review are as follows: 1) On-time performance affects passenger satisfaction; 2) Service quality affects passenger satisfaction; 3) Brand image affects passenger satisfaction; 4) Promotion affects passenger satisfaction; 5) On-time performance affects passenger loyalty; 6) Service quality affects passenger loyalty; 7) Brand image affects passenger loyalty; 8) Promotion affects passenger loyalty; 9) Passenger satisfaction affects passenger loyalty; 10) On-time performance affects passenger loyalty through passenger satisfaction; 11) Service quality affects passenger loyalty through passenger satisfaction; 12) Brand image affects passenger loyalty through passenger satisfaction; and 13) Promotion affects passenger loyalty through passenger satisfaction. This study is limited to passenger loyalty in the aviation sector. This study contributes to the understanding of factors influencing passenger loyalty, with a focus on factors such as on-time performance, service quality, brand image, promotion, and passenger satisfaction. This research provides new insights into other factors influencing passenger loyalty, particularly in the aviation industry. Thus, it can serve as a reference for future literature.   Keywords: Passenger Loyalty, Passenger Satisfaction, On-Time Performance, Service Quality, Brand Image, Promotion